Kajian tentang pola interaksi pelajar serta aktiviti pembelajaran berkesan dalam persekitaran pembelajaran atas talian bagi matapelajaran Fizik - Mohd. Ghanny, Irwan Shah (2013)
The purpose of this study is to examine students' interaction patterns as well as effective learning activities in an online learning environment for Physics . The topics chosen for this study was the Heat for Physics Form 4 for secondary school students in Malaysia . In this study , students were using e -learning methods to learn the chapter. The process takes about a month , and in each topic with notes , exercises, quizzes, assignments , discussions should be completed by each student . The evaluation is done by looking at the interaction of student learning, the frequency of students using e -learning, and scores on quizzes conducted . A total of 27 students who participated , and the researcher will classify students into three main classes, namely , weak , medium and high , according to the results of previous tests . The writer will take one of each of these categories and study their interaction. At the end of the study , the researcher will briefly interview sample to the validity of the study.